Momentary engagement in simultaneous versus consecutive interpreting: through the lens of translanguaging and CDST - Han, Lili; Lu, Jing; (Edward) Wen, Zhisheng; Tian, Yuan (Frontiers in Psychology, 2023)
Through the lens of translanguaging theory and the complex, dynamic system theory (CDST) approach, the interpreting process is considered a highly complex and dynamic activity that engages the interpreter’s cognition, emotion, and action during successive “translanguaging moments” of meaning-making. Meanwhile, the two dominant types of interpreting, namely, simultaneous interpreting, and consecutive interpreting are assumed to entail distinct time sensitivity and consume different amounts of cognitive resources at different stages. Based on these assumptions, the present study analyzes interpreters’ momentary engagement during the distinct workflow tasks associated with these two modes of interpreting, with a view to probing their underlying non-linearity, self-organization and emergence dynamics from a micro-level perspective. Furthermore, we triangulated the textual description with multimodal transcription to portray these “translanguaging moments,” which are augmented with a follow-up emotional survey that corroborated our findings.